HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN MAKANAN CEPAT SAJI PADA REMAJA - Anggoro, Arza Diwanto; manek, veny oktaviana; novianti, tria (Indonesian Journal of Nutrition Science and Food, 2024)
Fast food is food that is prepared and served quickly. Generally, these foods are high in calories, saturated fat, sugar, and salt, but low in fiber and other essential nutrients. Fast food is food that can be processed and served in a short time and easily in a matter of minutes. Fast food has two different meanings, but both refer to the rapid preparation and consumption of food. The purpose of this study is to find out the knowledge and attitude towards fast food in adolescents in Pekalongan district. Research shows that high consumption of fast food can lead to a decrease in nutritional status. This research was conducted using the cross sectional method, sampling was carried out by distributing questionnaires to respondents totaling 50 samples. Data analysis used univariate and bivariate tests to determine the frequency of knowledge and attitudes with fast food. Based on the results of the study, 28 female samples with a percentage of 54% and 22 male samples with a percentage of 46%. The increase in fast food consumption among teenagers is due to a modern lifestyle that prioritizes convenience and speed. Fast food is low in nutrition, and high in fat, sugar, and salt that negatively affects health including the risk of obesity, hypertension, and type 2 diabetes.